Traditional chinese culture poses dificulty for new animal welfare laws - WEI, Song (Revista Brasileira de Direito Animal, 2014)
Few people in China care about the feelings of animals or possess the concept of animal welfare. Some traditional factors play a positive role in this Weld From childhood, anything about animals, most Chinese children get in touch with has undoubtedly put man above them. Even some of the children’s songs have described the nature of animals as malicious, such as slippery fox and ruthless wolf and so on, which not only casts a dark shadow over their naïve hearts, but also leaves a wide gap between animals and children. It then appears in human ideology the discrimination of inferiority and superiority, eminence and humbleness, primary and secondary. These can all be taken in at a glance at the old saying Man is the master of the universe Disdain in spirit may lead to cruelty in action.